Pemanfaatan Media Teknologi Digital untuk Memberdayakan UMKM dan Melestarikan Kebudayaan Tradisional Desa Jangrana, Kesugihan, Cilacap - Muhammad Rizki Al Hasan; Bima Arya Pamungkas; Bintang Anggraini; Esthu Haryo Angandarto; Nicko Saputra Dwinar; Niken Ayuning Seputri; Putra Andriano Shafar; Qobitha Ocha Fishara Qoirunnisa; Yasmin Cikal Maharani; Zidan Muhamad Putranto; Budi Siswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The advancement of digital technology media has had a significant impact on various aspects of life, including in the economic cycle of the community and the preservation of local culture. One of them is in the utilization of digital technology in the economic sector which is growing rapidly and becoming an effective strategy in increasing village productivity. This study aims to analyze the results of the implementation of the Jangrana Village Festival work program related to how the integration of digital technology can contribute to the empowerment of local communities in the context of developing MSMEs and preserving traditional culture. The method used in this study is a qualitative approach with data collection techniques in the form of interviews, observations, and literature studies. The results of the study show that the application of digital technology, such as the use of Canva in creating MSME promotional instruments, village social media, and the digitalization of traditional cultural content, can strengthen the economic cycle and local cultural identity. In addition, the participation of local communities to be active as MSME activists also encourages economic and social sustainability. Therefore, a collaborative strategy between the government, levels of society, and digital industry players is needed to ensure the success of this program. Through these programs, it is hoped that it can be a learning experience for the present and also the future regularly and sustainably so that it can be useful for the people of Jangrana Village, Kesugihan.